2017
DOI: 10.7860/jcdr/2017/20132.10670
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Dosing Protocols of Anti-Snake Venom (ASV) in Snake Bite Cases

Abstract: The modified ASV protocol used in this study is more cost effective as compared to the conventional protocol, deserves prospective evaluation and may be followed at least during prime time of scarcity of ASV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…11,12 BR Daswani et al found that lower doses of ASV are as effective as the conventional high dose without being associated with higher mortality or morbidity. 13 This was in conformity with our results. Study by Paul V et al reported that high doses of ASV, apart from being nonsuperior and more costly, may at times turn out to be more harmful.…”
Section: Discussionsupporting
confidence: 93%
“…11,12 BR Daswani et al found that lower doses of ASV are as effective as the conventional high dose without being associated with higher mortality or morbidity. 13 This was in conformity with our results. Study by Paul V et al reported that high doses of ASV, apart from being nonsuperior and more costly, may at times turn out to be more harmful.…”
Section: Discussionsupporting
confidence: 93%
“…The percentage decreased in prospective year to 70 % reinforcing the fact that more initiatives are needed in increasing the awareness regarding snakebite in rural population. 4,6,11,13 Snakebites in the early morning and foot being the commonest site of bite followed by legs and upper limbs was seen in both years as has been recorded in other studies. 4,11 Polyvalent ASV remained the mainstay of snakebite victims in our country knowing the fact that it is only able to neutralise the free unbound toxins.…”
Section: Discussionsupporting
confidence: 78%
“…7,14,15 One of the objectives of implementation of National and WHO STG guideline on snakebite was to practice a rational use of ASV combat it scarcity. 7,13 The practice of ASV usage in primary health centre to every patient presenting with a history of snakebite decreased in prospective year when compared with the retrospective year. The unrestrained use of ASV in retrospective year unearthed the fact mentioned in various other studies that owing to fear of death of the patients, the attending physician resolve to use ASV injudiciously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] In viper bite rapid diagnosis and early administration of ASV may prevent venom induced coagulopathy and subsequent vascular complication including disseminated intravascular coagulation and renal failure. [18192021]…”
Section: Discussionmentioning
confidence: 99%